Siberia [videorecording (DVD)] - Ferrara, Abel, 1951-; Dafoe, Willem; Sichov, Dounia, 1980-; McBurney, Simon; Chiriac, Cristina (Lionsgate, 2021)
Clint tends bar at a snowbound roadhouse whose patrons speak a language he doesn't understand, and things may not be what they seem. Desperate for answers, he drives a sled team to a nearby cave, but finds no peace. Are the spirits that confront him mere figments of his imagination, or will they slowly tear his body and soul to pieces?